2021
DOI: 10.1038/s41467-021-23496-z
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanism of the human NHE1-CHP1 complex

Abstract: Sodium/proton exchanger 1 (NHE1) is an electroneutral secondary active transporter present on the plasma membrane of most mammalian cells and plays critical roles in regulating intracellular pH and volume homeostasis. Calcineurin B-homologous protein 1 (CHP1) is an obligate binding partner that promotes NHE1 biosynthetic maturation, cell surface expression and pH-sensitivity. Dysfunctions of either protein are associated with neurological disorders. Here, we elucidate structures of the human NHE1-CHP1 complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(128 citation statements)
references
References 71 publications
9
119
0
Order By: Relevance
“…Na + /H + exchangers form physiological homodimers 2 , 21 , with the monomers made up of a 6-transmembrane (TM) ion-translocation domain (or core domain) and a dimerization domain 22 27 . Recent structures of mammalian NHE1 25 and NHE9 23 were found to be highly similar to bacterial Na + /H + antiporter structures with 13 TMs 22 , 24 , 26 , 28 . So far, the core domain has proven to be structurally similar, with most of the structural divergence in the dimerization domain instead 23 .…”
Section: Mainmentioning
confidence: 90%
See 1 more Smart Citation
“…Na + /H + exchangers form physiological homodimers 2 , 21 , with the monomers made up of a 6-transmembrane (TM) ion-translocation domain (or core domain) and a dimerization domain 22 27 . Recent structures of mammalian NHE1 25 and NHE9 23 were found to be highly similar to bacterial Na + /H + antiporter structures with 13 TMs 22 , 24 , 26 , 28 . So far, the core domain has proven to be structurally similar, with most of the structural divergence in the dimerization domain instead 23 .…”
Section: Mainmentioning
confidence: 90%
“…So far, the core domain has proven to be structurally similar, with most of the structural divergence in the dimerization domain instead 23 . Na + /H + exchangers operate by an ‘elevator’ alternating-access mechanism 23 25 , 29 , 30 . In an elevator mechanism, the ion is transported by the core domain against the dimerization domain, which remains fixed due to oligomerization 30 .…”
Section: Mainmentioning
confidence: 99%
“…It also represents the inner acid base chemistry that consumes or generates the transported acid-base equivalents. of NHE1 and nine structures in (Winklemann et al, 2020;Dong et al, 2021). Other important structures have been obtained by X-ray diffraction, for AE1 in (Arakawa et al, 2015), and for monocarboxylate transporters (Bosshart et al, 2019;Zhang et al, 2020).…”
Section: More Than 63 Genes Encode Ph Regulatory Plasma Membrane Prot...mentioning
confidence: 99%
“…zoniporide, rimeporide, cariporide and benzoylguanidine 16 , 17 or (furan-2-ylcarbonyl)guanidines 18 derivatives, respectively. Structure of cariporide/NHE-1 complex was recently solved using cryo-EM 19 . It was demonstrated that acylguanidine moiety plays a crucial role in the binding.…”
Section: Introductionmentioning
confidence: 99%